Journey into the Sicilian gastro-sphere - Ventura Bordenca, Ilaria (E|C, 2020)
This paper presents the analysis of a type of Sicilian street food known in Palermo as “rosticceria”. It is a coherent and composite set of dishes that are part of a local, popular and economic gastronomy, and with a highly practical function of "food supply". Through an internal analysis of the “rosticceria”, considering the elements that compose it and the relationships between them, as well as through a comparison with other gastronomic universes, we will see how it is possible to identify the deep semiotic forms that govern the socio-cultural functioning of this common food of the gastronomy of the city of Palermo.